International Journal of Maritime Engineering 2018
DOI: 10.3940/rina.ijme.2018.a1.439
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for a Wind Assisted Ship Propulsion

Abstract: For three different wind propulsion technologies, the energy saving potential of sea going cargo vessels are discussed: a kite, a Flettner rotor and a Dynarig-sail. The energy saving potential can be increased significantly if the route can be optimized when using a wind assisted ship propulsion. The increase of travelling time due to a route adoption is within the frame of the commonly accepted uncertainty in supply chains and can be limited or adjusted in the route optimization software as a parameter. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Numerous recent studies have focused on the modeling and the simulation of wind assisted propulsion systems (e.g, Rosander & Bloch 2000;Bentin et al 2018;Talluri et al 2018), while potential fuel savings have been demonstrated by 3-DOF (Viola et al 2015;Ma et al 2023) and 4-DOF (Tillig & Ringsberg 2019) simulation methods. Although the main focus has been given to the performance prediction of vessels equipped with Wind Assisted Propulsion Systems (WAPS), the effect of WAPS on ship design optimization has not been yet systematically examined, namely traditional ship design concepts are being equipped with WAPS in the way of retrofitting and their performance is examined/optimized, even if they are newbuildings.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous recent studies have focused on the modeling and the simulation of wind assisted propulsion systems (e.g, Rosander & Bloch 2000;Bentin et al 2018;Talluri et al 2018), while potential fuel savings have been demonstrated by 3-DOF (Viola et al 2015;Ma et al 2023) and 4-DOF (Tillig & Ringsberg 2019) simulation methods. Although the main focus has been given to the performance prediction of vessels equipped with Wind Assisted Propulsion Systems (WAPS), the effect of WAPS on ship design optimization has not been yet systematically examined, namely traditional ship design concepts are being equipped with WAPS in the way of retrofitting and their performance is examined/optimized, even if they are newbuildings.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] New solutions may include electric propulsion, 20,21 hybrid solutions, 22 fuel cell driven propulsion, [23][24][25][26] carbon capture technologies, [27][28][29] alternative fuels, 13,[30][31][32][33][34][35] sailing, and wind/wave/solar assisted vessel operation. [36][37][38][39][40] All proposed systems have different environmental performance, technical limitations, and economic prerequisites. Moreover, combinations of new systems will be required to reach the global environmental targets 17 proposed by the International Maritime Organization (IMO).…”
Section: Introductionmentioning
confidence: 99%